Mendeley: An Introduction To Online Citation In Writing Research Article As The Implementation Of The Three Missions Of Universities At Nasional University - Nico Harared; Sugianti Somba; Fajar Wahyudi Utomo (Edumedia Solution, 2022)
This present community service activity aims at giving an understanding of the use of Mendeley application comprehensively in a research article for the lecturers of the Faculty of Language and Literature at Nasional University. The method of implementing this activity was divided into three steps in workshops model: (1) practical guidelines and tips on how to write at national accredited journals, (2) introducing Mendeley, and (3) practice of Mendeley. The result of the community service activity indicates that this activity help the lecturers in the citation writing process in case of in writing bibliography. Mendeley makes writing bibliography more effective and efficient. In understanding the citation process, verification will be more accurate and easier for other researchers to trace research. From these result, it can be concluded that this activity needs an intensive socializations on the use of Mendeley as an application of citations. The lecturers get the positive impact of this activity. The positive feedback of the lecturers was shown interactively during the implementation activities. It can be seen through their testimonials.